A comparison of women’s expectations of labour and birth with the experiences in primiparas and multiparas with normal vaginal delivery - Pirdil, Manijeh; Pirdel, Leila (Journal of Kathmandu Medical College, 2016)
Background: Maternal childbirth expectations play an important role in determining a woman’s response to her childbirth experience. Women need to be helped to develop realistic and positive expectations and identify the factors that influence these expectations.Objective: The aim of this study was to compare woman’s expectations and experiences of childbirth.Methods: This descriptive-comparative study was carried out in Tabriz Alzahra Hospital from 2006 to 2007. For this purpose, a total of 600 primiparas and multiparas women who were candidates for vaginal delivery, were randomly selected and interviewed. The data were collected by questionnaire.Results: Comparison of the means of mothers expectation and experience of labor and birth between the two groups demonstrated a statistically significant difference (p